Field evaluations on soil plant transfer of lead from an urban garden soil - Attanayake, Chammi P.; Hettiarachchi, Ganga M.; Harms, Ashley; Presley, DeAnn R.; Martin, Sabine E.; Pierzynski, Gary M. (My University, 2014)
Lead (Pb) is one of the most common contaminants in urban soils. Gardening in contaminated soils can result in Pb transfer from soil to humans through vegetable consumption and unintentional direct soil ingestion. A field experiment was conducted in 2009 and 2010 in a community urban garden with soil total Pb concentration of 60 to 300 mg kgˉ¹. The objectives of this study were to evaluate soil-plant transfer of Pb, the effects of incorporation of a leaf compost as a means of reducing Pb concentrations in vegetables and the bioaccessibility of soil Pb, and the effects of vegetable cleaning techniques on the Pb concentrations in the edible portions of vegetables. The amount of compost added was 28 kg mˉ². The tested plants were Swiss chard, tomato, sweet potato, and carrots. The vegetable cleaning techniques were kitchen cleaning, laboratory cleaning, and peeling. Compost addition diluted soil total Pb concentration by 29–52%. Lead concentrations of the edible portions of vegetables, except carrot, were below the maximum allowable limits of Pb established by FAO and WHO. Swiss chard and tomatoes subjected to kitchen cleaning had higher Pb concentrations than laboratory-cleaned plants. Cleaning methods did not affect Pb concentrations in carrots. Bioaccessible Pb in the compost-added soils was 20–30% less than that of the no-compost soils; compost addition reduced the potential of transferring soil Pb to humans via vegetable consumption and direct soil ingestion. Thorough cleaning of vegetables further reduced the potential of transferring soil Pb to humans.
Citaion: Attanayake, Chammi P., et al. “Field Evaluations on Soil Plant Transfer of Lead from an Urban Garden Soil.” Journal of Environmental Quality, vol. 43, no. 2, 2014, pp. 475–87. Wiley Online Library, doi:10.2134/jeq2013.07.0273.
Keywords: Urban soil; Lead; Soil-plant transfer; Bioaccessibility